Effects of Thai Traditional Massage on Onset and Duration of First Stage of Labor: A Randomized Controlled Trial - Chaichan, Atchara; Phumdoung, Sasitorn (Pacific Rim International Journal of Nursing Research, 2021)
Various methods of labor induction are recommended for stimulating the onset of labor. However, these methods produce adverse effects. Massage is a safe alternative method for labor induction and shortens the duration of labor, as it can promote oxytocin release. Thus, a randomized controlled trial with single-blind technique was used to investigate the effects of Thai traditional massage on the onset and duration of the first stage labor. Participants were primiparous women. A minimized randomization program was used to assign the participants into experimental or control groups. The experimental group (n = 24) received 40 minutes of Thai traditional massage once a week when they reached 37 weeks of gestation until either reaching 40 weeks or starting labor onset. The control group (n = 27) received usual care. The period of the onset of labor was measured by the duration in hour from 37 weeks of gestation to the starting of regular uterine contractions at least 2-3 times per hour, and the duration of first stage of labor was measured by the period in hour start from onset of labor to the full cervical dilation (10 centimeter). Descriptive statistic, chi-square tests, and independent t-tests were used to analyze the data. The results showed that applying Thai traditional massage once a week is not sufficient for inducing the onset of labor. However, the duration of first stage labor in experimental group was significantly shorter than control group. Thus, nurses or pregnant woman’s husband and relatives could be trained to apply Thai traditional massage to lower duration of labor.